Invasive slipper limpets (Crepidula fornicata) act like a sink, rather than source, of Vibrio spp. - Emma Quinn (Biological Invasions, 2022)
A large knowledge gap exists regarding the disease profile and pathologic condition of the invasive, slipper limpet Crepidula fornicata. To help address this, we performed a year-long health survey at two sites in South Wales, UK – subtidal Swansea Bay and intertidal Milford Haven. In total, 1,800 limpets were screened systematically for haemolymph bacterial burdens using both general and vibrio-selective growth media (TSA + 2% NaCl and TCBS, respectively), haemolymph (blood) inspection using microscopy, a PCR-based assay targeting Vibrio spp., and multi-tissue histology. Over 99% of haemolymph samples contained cultivable bacterial colony-forming units, and 83% of limpets tested positive for the presence of vibrios via PCR (confirmed via Sanger sequencing). Vibrio presence did not vary greatly between sites, yet a strong seasonal effect was observed with significantly higher bacterial loads during the summer. Binomial logistic regression models revealed larger (older) limpets were more likely to harbour vibrios, and the growth of bacteria on TCBS was a key predictor for PCR-based vibrio detection. Histological assessment of > 340 animals revealed little evidence of inflammation, sepsis or immune reactivity despite the gross bacterial numbers. We contend that slipper limpets are not highly susceptible to bacteriosis at either site, and do not harbour vibrios known to be pathogenic to humans. The lack of susceptibility to local pathogenic bacteria may explain, in part, the invasion success of C. fornicata across this region.